The Specificity of the Arbitration Agreement in Contracts Concluded by Public Moral Persons in the Field of International Economic Relations [In Arabic] - Hitoum, Mesaoud (Milev Journal of Research and Studies, 2022)
Peoples have known the arbitration system since ancient times, and it was initially limited to resolving existing disputes or that could arise in private contractual and non-contractual relations, while arbitration in public contracts did not spread and was not known until after the urgent need dictated it, so this study deals with the specifics of The arbitration agreement concluded by public legal persons, and how the various aspects that usually deal with arbitration appear, and the extent to which that corresponds to administrative contracts. On the other hand, we noticed how the state has the means that enable it to highlight its privileges, especially when the arbitration agreement contradicts the idea of ​​sovereignty, as well as the issue of public order, which is the safety valve for this agreement, in addition to the issue of judicial oversight over the arbitral award and its important role, and the administrative contract has a special system The arbitration agreement seeks to establish a special system and herein lies the contradiction that can be reduced through legislative mechanisms and an agreement with the contracting party.